Identifikasi Wilayah Resiko Kerusakan Lahan Terbangun Sebagai Dampak Tsunami Berdasarkan Analisis Building Indices - Permatasari, Aurilia Dinda; Joko Prasetyo, Sri Yulianto (Jurusan Teknologi Informasi Universitas Semarang, 2022)
Indonesia has a very large water area and there is the territory that is the confluence of the earth's slabs. It can allowing the occurrence of tsunami natural disasters. The study aims to find out which areas have risks the highest and the lowest land damage. The data used in this study were satellite images taken from 2014-2021 with coverage area in Kulon Progo Regency which consists of 12 sub-districts. This study used indexes vegetation UI, NDBI, IBI, EBBI. With an ANN algorithm get results which is quite accurate with an accuracy rate of 94.50%. Predictions states that the area has a high risk of damage due to the tsunami, namely the villages of Jingkaran, Sindutan, Palihan, Glagah, Karangwuluh, Janten, Temon Kulon, Kedundang, Sogan, Kalidengen, Ngestiharjo, Depok, Kanoman, Panjatan, Wahyuharjo, Pandowan, Nomporejo, and, Kranggan.